Mechanism and countermeasures of "The innovator's dilemma" in business model - Chengbin Wang; Yongyan Fang; Chuan Zhang (Journal of Innovation & Knowledge (JIK), 2022)
Business model innovation is an important field in enterprise innovation, both as a necessary tool as well as a source of innovation. This study analyzes two business model innovations of Suning and their effects, and finds that enterprises will also face the innovator's dilemma when they carry out business model innovations. By introducing environmental variables into the decision interval model, this study explores the conduction path and mechanism to explain the innovator's dilemma from a new perspective, and calls on the academic to strengthen research on environmental variables to adapt to the VUCA era. The S-curve analysis implies that when enterprises encounter the innovator's dilemma the key lies in whether they can cross the discontinuity gap and successfully open the second S-curve. To deal with this, enterprises can form a closed loop of feedback iteration through insight problems, seeking solutions, and verifying solutions to explore the direction of business model transformation, and promote business model innovation in an orderly manner by implanting a "central control system" and commissioning a "radar system".
Keywords: 650; Business model; Lean method; S-curve; Suning company; The innovator's dilemma